Reading comprehension beliefs of Mexican pre-service language teachers: a Likert scale study - Moisés Damián Perales-Escudero; Mizael Garduño Buenfil; Vilma Esperanza Portillo Campos (Universidad ORT Uruguay, 2023)
This paper aims to report the adaptation of a new version of the Scale of Implicit Theories of Reading Comprehension (ETICOLEC as per its Spanish acronym) with a sample of 77 randomly chosen English majors at a peripheral campus of a small university in the Southeast of Mexico. The ETICOLEC Likert scale was originally designed to measure the reading comprehension beliefs of middle school teachers of several subjects. Hence, it was necessary to adapt it to identify the beliefs of pre-service language teachers. A standard procedure recommended by the literature (Prat & Doval, 2005) was used to add new items to the scale and test its psychometric properties using principal component analysis and internal consistency analysis with Cronbach´s alpha. Calculations were performed using the Statistical Package for the Social Sciences (SPSS, v. 26). As with the original ETICOLEC, this adapted version yielded five internally consistent sub-scales, albeit slightly different from the original ones. Each subscale measures an implicit theory or group of beliefs about reading comprehension. As a secondary, exploratory goal, we also describe the participants according to their implicit theories. Most participants held implicit theories that are functional for the kinds of epistemic reading tasks required by their university education. However, a large minority did not appear to hold any firm beliefs about reading, suggesting insufficient exposure to various complex reading tasks and genres. This situation must be addressed to ensure these pre-service teachers become effective reading teachers.